Decoding thymic development: a single-cell atlas of tree shrew immunity - Tang, Haibo; He, Yunlin; Zhang, Lifeng; Cao, Yingying; Li, Baoying; Liang, Liang; Yun, Chengxia; Tao, Junyu; Zhai, Shanshan; Li, Zhuxin; Dai, Yinghan; Hu, Yanling; et al. (Frontiers in Immunology, 2026)
The tree shrew is a potential mammalian model for preclinical studies, but its immune system is not well understood. In this study, we utilized single-cell RNA sequencing (scRNA-seq) to construct a comprehensive cell atlas of the postnatal thymus development of the tree shrew. Our data revealed that the tree shrew thymocytes exhibit conserved features with species-specific variations in cell states and types when compared to those of humans and pigs. We found that tree shrew thymocyte markers are generally intermediate between humans and pigs, with some resembling each species. Some are different from both humans and pigs, such as the expression of the ZNF683 gene, which is not detected until the later stage of CD8aa cells development. The tree shrew thymic cells were classified into 20 types based on gene expression, confirming previous findings of basic thymic immune cells in tree shrews. The results show that immature immune cells were present in a higher proportion in young tree shrews compared to old ones. As tree shrews mature, there was a significant increase in the proportion of late-differentiated functional cells, such as Treg cells. A pseudo-temporal analysis revealed that thymocytes in tree shrews predominantly originated from a common starting point, with the exception of B and dendritic cells. A pseudotime trajectory analysis identified 17 gene modules, aligning with known T cell development stages and markers. Aging-related transcriptional changes in tree shrew thymus cells initially rise and then fall with age. Older tree shrews show increased expression of aging-related genes and decreased or absent anti-aging genes. These findings elucidate key differentiation events in the maturation of thymopoiesis in tree shrews and offer valuable insights into the development of T cells in this species.